Factors predicting of the Implant Contraceptive Used as Family Planning Method among Mothers in Wae Mbeleng Public Health Center, Ruteng Sub District - Dionesia Octaviani Laput; Stefanus. P Manongga; Muntasir Muntasir; Eufrasia Prinata Padeng; Fransiska Nova Nanur (International Journal of Nursing and Health Services (IJNHS), 2021)
To achieve optimal maternal health is one of the development agenda in line with the Sustainable Development Goals (SDGs). The said agenda also in line with the government development pathway 2015-2019, to manifest the development priority agenda (Nawacita), particularly on the fifth point namely “increasing the quality of life of Indonesian” through “population development and family planning”. This study aim to identify factors related to the use of implant as contraceptive family planning method in Wae Mbeleng public health center. This study was using analytic cross-sectional design on 392 women on reproductive age selected using multistage random sampling. The variable analyzed in this study such as age characteristic, information from health professionals and spouse’ support collected using structurized questionnaire from January 2019 to March 2019. Data analysis conducted through univariate analysis, bivariate analysis using simple logistic regression test and multivariate analysis using multinomial logistic regression. The study identified that the prevalence of implant use on reproductive age women in Wae Mbeleng public health center was 0,9%. Variables with significant statistic correlation on implant use were age (p=0,005), education (0,000), knowledge (0,000), culture (0,016), information obtain from health professionals (p= 0,000), and spouse’s support (p=0,000). The most impactful variable on implant contraceptive method was the information obtain from health workers. The effort to facilitate the information provision is by engaging public figure and religious leader that considered as role models in order to avoid the misinterpretation of family planning in accordance with each religious beliefs. Kata kunci: reproductive age women, implant